Helmut Lachenmann: Salut für Caudwell / Les Consolations / Concertini - Lachenmann, Helmut 1935-; Kalitzke, Johannes; Bruck, Wilhelm; Ross, Theodor; Schola Heidelberg; WDR Sinfonieorchester Köln (Wien KAIROS, 2008)
HELMUT LACHENMANN Les ConsolationWilhelm Bruck guitar / Theodor Ross guitarSCHOLA HEIDELBERG / Walter NußbaumWDR Sinfonieorchester Köln / Johannes KalitzkeKlangforum WienIncludes booklet with text by Helmut Lachenmann0012652KAI - 2009 - 2CD tracklisting:CD1(01) Salut für Caudwell (1977) Musik für zwei Gitarristen 25:14Les Consolations (1967-68/1977-78) für 16 Stimmen und Orchester(02) I. Präludium 5:55(03) II. Consolation I 8:48(04) III. Interludium 4:51(05) IV. Consolation II 6:10(06) V. Postludium 6:34TT: 57:41CD2(01) Concertini (2005) für Ensemble 37:06TT: 37:06What I want...is always the same: a music which in order to be grasped, does not require a privileged intellectual training, but can rely uniquely upon its compositional clarity and logic; a music which is at the same time the expression and the aesthetic form of a curiosity able to reflect everything including the illusion of progressiveness. Art as a foretaste of freedom in an age without freedom.(Interview with Ursula Stürzbecher, 1971)